The Impact of Peer-to-Peer (P2P) Lending on Business Development of Small and Medium-Sized Enterprises - Duhita Paramaramya Putri Nurdana; Rindah Febriana Suryawati (TIJAB (The International Journal of Applied Business), 2021)
The problem faced by most micro-entrepreneurs in Indonesia is financing business. Peer-to-peer (P2P) lending is a non-bank financial institution that can be an alternative source of financing because of the requirements and easy application usage. This study aims to analyze the impact of peer-to-peer lending on business expenses, business turnover, total employment, total sales of products, and profits before and after obtaining a peer-to-peer lending loan and analyze factors affecting the increase in business turnover after getting a loan through peer-to-peer lending. The methods used in this study include the descriptive analysis method, paired t-test, and ordinary least square (OLS). The paired t-test results indicate that there is a significant difference between business expenses, business turnover, the amount of labor, the number of product sales, and profit before and after obtaining a peer-to-peer lending loan. The result of analysis with the OLS method shows that the length of business and expenditure of the business has a significant effect on the development of respondents' business turnover.